2008
DOI: 10.4161/psb.3.5.5352
|View full text |Cite
|
Sign up to set email alerts
|

Are there multiple circadian clocks in plants?

Abstract: The plant circadian clock controls a multitude of physiological processes such as photosynthesis, organ and stomatal movements and transition to reproductive growth. A plant clock that is correctly matched to the rhythms in the environment brings about a photosynthetic advantage that results in more chlorophyll, more carbon assimilation and faster growth. 3 One of the first circadian clock mutants to be described in plants was the short period timing of cab1-1 (toc1-1), which was identified using the rhythms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…This disconnection could result from the presence of multiple oscillators or tissue-specific differences in the expression of FKF1 and CAB2 (51,52). FKF1 is expressed in both vascular bundles and mesophyll cells whereas CAB2 is expressed in mesophyll cells and epidermal guard cells (53,54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This disconnection could result from the presence of multiple oscillators or tissue-specific differences in the expression of FKF1 and CAB2 (51,52). FKF1 is expressed in both vascular bundles and mesophyll cells whereas CAB2 is expressed in mesophyll cells and epidermal guard cells (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…Both genes respond differently to temperature signals although the spatial expression patterns of CAB2 and CAT3 overlap in the mesophyll. The toc1-1 mutant has short period rhythms of CAB2 but has a wild-type period for cytosolic Ca 2+ oscillation whereas the toc1-2 mutant has a short period for both CAB2 and Ca 2+ rhythms, which suggests that different mechanisms regulate the rhythms of CAB2 and Ca 2+ (52). We contemplated the possibility that because CAB2 is involved in photosynthetic responses and may be exposed to ROS fluctuations, its rhythms are buffered from ROS responses by some mechanism-perhaps a second oscillator.…”
Section: Discussionmentioning
confidence: 99%
“…, 2003). It has been suggested that these differences in circadian phenotypes of gene expression show that TOC1 might interact with different proteins in a cell‐type specific manner (Hotta et al. , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In the toc1-1 line, LHCB in red light and GLYCINE RICH RNA BINDING PROTEIN7 (ATGRP7/CCR2) in the dark are expressed with a shorter period, while under the same conditions the genes are arrhythmic in toc1-2 plants (Somers et al, 1998;Strayer et al, 2000;Mas et al, 2003). It has been suggested that these differences in circadian phenotypes of gene expression show that TOC1 might interact with different proteins in a cell-type specific manner (Hotta et al, 2008). However, the most compelling evidence for differences in molecular composition of oscillators in different cell/organ types comes from a report showing that in roots, unlike in shoots, oscillator function does not require rhythmic expression of key circadian genes such as TOC1 (James et al, 2008).…”
Section: Guard Cells Have Different Circadian Rhythmsmentioning
confidence: 99%
“…Furthermore, the molecular composition of circadian clocks can differ between various cell and organ types. Thus, PRR3 modulates TOC1 stability in vasculature cell types, but not in others; CCA1 and LHY are not able to inhibit TOC1 expression in dark-grown roots (further examples in Harmer 2010; Hotta et al 2008).…”
Section: Clock Mechanism and Clock-controlled Genesmentioning
confidence: 99%